Preparation method of PEM water vapor electrolytic cell membrane electrode with high moisture mass transfer coefficient

By increasing the water content of the catalytic layer in the PEM water vapor electrolytic cell and adjusting the pore structure, combining a high water-retaining proton exchange membrane and a hydrophilic catalytic layer, the problem of low membrane electrode transfer efficiency is solved, and more efficient electrolytic and dehumidification performance is achieved.

CN119824442APending Publication Date: 2025-04-15SOUTH CHINA UNIV OF TECH +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510300824.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-14
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

The electrolytic water vapor reaction efficiency of existing PEM water vapor electrolytic cells is low, mainly due to the slow water vapor/proton transfer efficiency of membrane electrodes, resulting in limited reaction rate.

Method used

By increasing the water content in the catalytic layer and adjusting the pore structure to improve the water vapor diffusion coefficient, a PEM water vapor electrolytic cell membrane electrode with a high moisture mass transfer coefficient was prepared using a combination of a high water-retaining proton exchange membrane and a hydrophilic catalytic layer.

Benefits of technology

It improves the electrolytic effect, enhances the dehumidification performance, meets the needs of deeper dehumidification, and performs better in low-temperature environments and low-humidity conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119824442A_ABST
    Figure CN119824442A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a PEM water vapor electrolytic cell membrane electrode with a high moisture mass transfer coefficient, and belongs to the technical field of PEM water vapor electrolytic cells. Immersing the perfluorosulfonic acid membrane in a methanol / aqueous solution for swelling, taking out the perfluorosulfonic acid membrane, and immersing the perfluorosulfonic acid membrane in a methanol / tetraethyl silicate solution for an in-situ sol-gel reaction to obtain the high-water-retention proton exchange membrane; a metal anode catalyst, a perfluorosulfonic acid ionomer, silicon dioxide and a solvent are mixed and dispersed into uniform slurry, and the uniform slurry is loaded on one side of a high-water-retention proton exchange membrane to form an anode hydrophilic catalyst layer; a metal cathode catalyst, a perfluorosulfonic acid ionomer and a solvent are mixed and dispersed into uniform slurry, and the slurry is loaded on the other side of the high-water-retention proton exchange membrane to form a cathode catalyst layer; a cathode gas diffusion layer and an anode gas diffusion layer are attached to the cathode catalyst layer and the anode catalyst layer respectively, and the membrane electrode is obtained. The electrolytic water vapor membrane electrode with high dehumidification performance is prepared and used for a PEM water vapor electrolytic bath, the dehumidification depth can be increased, and application with higher requirements can be met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of PEM water vapor electrolyzers, and in particular to a method for preparing a PEM water vapor electrolyzer membrane electrode with a high water mass transfer coefficient. Background Art

[0002] When the PEM water vapor electrolyzer is operated at an applied voltage of 1.5~3V, gaseous water undergoes electrolysis at the membrane electrode anode to decompose into O2 and H + , the generated H + When the cathode is liquid water or inert gas (such as N2), hydrogen is generated after passing through the proton exchange membrane. If the cathode is air or oxygen, water is generated again after the reaction. PEM water vapor electrolyzer has the following significant advantages: (1) The equipment structure is simple and the volume is small, which can reach the cubic centimeter level; (2) No condensation water is generated during operation, and there is no mold growth, water leakage and other problems; (3) The electrolysis rate can be adjusted by changing the voltage to achieve rapid switching between water removal and water production; (4) Low voltage drive, normal temperature and pressure can be operated, and it can be combined with clean energy technologies such as photovoltaic power generation. Therefore, it has wide application potential in both high-tech development and life scenarios. For example, by adjusting the water molecule content in a large range to control humidity, the humidity control requirements under different scenarios and conditions can be met. In the operation of precision equipment such as infrared spectrometers, electron microscopes and other optical instruments, humidity control is very important for stability and measurement accuracy. Excessive humidity can cause problems such as sample moisture absorption, optical components dampness, and water vapor interference. However, the internal space of precision instruments is small, so only humidity control methods that occupy a small volume can be adapted. The use of desiccant has the problem of needing to be replaced regularly. In terms of item preservation, valuable items such as cameras, red wine, and paper artifacts have certain requirements for humidity, and the range is wide. PEM water vapor electrolyzers can accurately control the humidity within the required range. On the other hand, it can be combined with membrane distillation, interfacial evaporation and other technologies to produce hydrogen from seawater. PEM water vapor electrolyzers have great development prospects due to their unique advantages.

[0003] However, the efficiency of the electrolysis of water vapor in PEM water vapor electrolyzers is currently low, which is mainly limited by the slow water vapor / proton transfer efficiency of the membrane electrode. The reaction rate is significantly affected by the mass transfer efficiency. High mass transfer efficiency means that water vapor can quickly contact the catalytic active sites to produce oxygen evolution electrochemical reactions, and ensure that the solid electrolyte is in a wet state to form a proton transport network to accelerate the transfer, ultimately increasing the dehumidification rate. Therefore, increasing the mass transfer rate of the membrane electrode to enhance the dehumidification capacity is the key to promoting the commercialization of PEM water vapor electrolyzers.

[0004] At present, the membrane electrode of the PEM water vapor electrolyzer uses polyelectrolytes such as perfluorosulfonic acid as the solid electrolyte membrane and the proton conductor in the catalyst layer, and its proton conductivity is linearly related to its water content, which directly affects the performance of the PEM water vapor electrolyzer. Especially for the anode catalyst layer of the PEM water vapor electrolyzer, water vapor is both a reactant and a hydrating agent for the proton conductor ionomer in the catalyst layer. High water vapor mass transfer efficiency can ensure sufficient contact with the catalyst, which is conducive to the oxygen evolution reaction. On the other hand, it can keep the solid electrolyte in a good hydration state, build a continuous proton transmission channel, and improve the reaction rate of the water vapor electrolyzer. Therefore, it is necessary to adopt appropriate methods to improve the water vapor mass transfer inside the catalyst layer. The mass transfer capacity of water vapor in the anode catalyst layer is an important factor limiting the reaction.

[0005] The transport resistance of the reactant (water vapor) when it reaches the anode catalyst layer to react and the speed of proton transfer through the ionomer are the key factors that determine the reaction rate. Water vapor diffuses through the pores in the catalyst layer structure, then penetrates the ionomer film covering the catalyst surface to participate in the reaction, and then the ionomer conducts protons. The proton transfer ability of the ionomer mainly depends on the hydration network formed by the hydrophilic side chain. A moderately humid environment helps the ionomer absorb water molecules and enhance the proton transfer ability, while excessive moisture will cause the ionomer to swell, block the pores and increase the diffusion resistance. Therefore, the relationship between the two needs to be balanced in the design of optimizing performance. When the temperature is below 20°C or the relative humidity is below 60%RH, the water vapor flux entering the active site of the catalyst is small, resulting in a decrease in device performance. This is because insufficient feed leads to insufficient hydration of the membrane and catalyst layer, which seriously affects the construction of the proton transport network. Therefore, water vapor quickly reaches the anode of the PEM water vapor electrolyzer and wets the PEM and catalyst layer without affecting the diffusion of water vapor, which can improve the electrolysis capacity of the system and thus accelerate the dehumidification rate, which is conducive to the commercialization of dehumidification devices using PEM water vapor electrolysis. Summary of the invention

[0006] The purpose of the present invention is to provide a method for preparing a PEM water vapor electrolyzer membrane electrode with a high water mass transfer coefficient. By increasing the water content in the catalytic layer and adjusting the pore structure to improve the water vapor diffusion coefficient, a membrane electrode with better electrolysis effect can be obtained, the dehumidification effect of the device can be increased, and deeper dehumidification requirements such as low temperature environment and low humidity can be met. At the same time, the preparation method is simple and has good application value.

[0007] To achieve the above object, the present invention provides a method for preparing a PEM water vapor electrolyzer membrane electrode with a high water mass transfer coefficient, which specifically comprises the following steps: (1) Preparation of high water retention proton exchange membrane The perfluorosulfonic acid membrane is dried, then immersed in a methanol / water solution for swelling, taken out, and then immersed in a methanol / tetraethyl silicate solution for in-situ sol-gel reaction. After the reaction is completed, the membrane is taken out for drying to obtain a high water-retention proton exchange membrane; (2) Preparation of anode hydrophilic catalytic layer The metal anode catalyst, perfluorosulfonic acid ionomer, silicon dioxide and solvent are mixed and dispersed into a uniform catalyst slurry, which is loaded on one side of the high water retention proton exchange membrane obtained in step (1), and dried to form an anode hydrophilic catalyst layer; (3) Preparation of cathode catalyst layer Mixing and dispersing a metal cathode catalyst, a perfluorosulfonic acid ionomer and a solvent into a uniform catalyst slurry, loading the slurry on the other side of the high water retention proton exchange membrane obtained in step (1), and drying the slurry to form a cathode catalyst layer; (4) Preparation of PEM water vapor electrolyzer membrane electrode The anode gas diffusion layer and the cathode gas diffusion layer are respectively bonded to the catalyst layers obtained in step (2) and step (3), thereby obtaining a PEM water vapor electrolyzer membrane electrode.

[0008] Preferably, in step (1), the volume ratio of methanol to water in the methanol / water solution is 1-4:1-3, and the volume ratio of methanol to tetraethyl silicate in the methanol / tetraethyl silicate solution is 2-6:1-3.

[0009] Preferably, in step (1), the thickness of the perfluorosulfonic acid film is 127 μm; the drying condition of the perfluorosulfonic acid film is drying in a vacuum drying oven at 80° C. for 12 h; and the drying condition after the reaction is completed is drying in a vacuum drying oven at 80° C. for 48 h.

[0010] Preferably, in step (2), the loading amount of the metal in the metal anode catalyst on the high water retention proton exchange membrane is 1.3 mg / cm 2 .

[0011] Preferably, in step (2), the mass ratio of the metal anode catalyst to the perfluorosulfonic acid ionomer is 4:1, and silicon dioxide accounts for 0%-10% of the total mass of the metal anode catalyst and the perfluorosulfonic acid ionomer.

[0012] Preferably, in step (2), the particle size of silicon dioxide is 20 nm; the metal anode catalyst is iridium dioxide; the perfluorosulfonic acid ionomer is 5 wt.% Nafion; and the solvent is a mixed solution of isopropanol and water.

[0013] Preferably, in step (3), the loading amount of the metal in the metal cathode catalyst on the high water retention proton exchange membrane is 0.2 mg / cm 2 .

[0014] Preferably, in step (3), the mass ratio of the metal cathode catalyst to the perfluorosulfonic acid ionomer is 1.78:1.

[0015] Preferably, in step (3), the metal cathode catalyst is a 20% carbon-supported platinum catalyst; the perfluorosulfonic acid ionomer is 5wt.% Nafion; and the solvent is a mixture of isopropanol and water.

[0016] Preferably, in step (4), the anode gas diffusion layer is a titanium mesh; and the cathode gas diffusion layer is a carbon paper treated with polytetrafluoroethylene for hydrophobicity.

[0017] Therefore, the present invention provides a method for preparing a PEM water vapor electrolyzer membrane electrode with a high water mass transfer coefficient, obtaining a proton exchange membrane with better water retention performance and faster proton conduction, obtaining a membrane electrode catalytic layer with high water vapor utilization rate and water diffusion efficiency, and an electrolytic water vapor membrane electrode with high dehumidification performance, which can be used in a PEM water vapor electrolyzer to increase the dehumidification depth and meet applications with higher requirements. At the same time, the preparation method is simple and has good application value.

[0018] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 It is a schematic diagram of the water and proton transport in the anode catalyst layer of the water vapor electrolysis membrane assembly; Figure 2 This is a scanning electron microscope (SEM) image of the hydrophilic anode catalyst layer prepared in Example 6 of the present invention; Figure 3 It is the adsorption isotherm of the hydration coefficient of the PEM / SiO2 proton exchange membrane obtained in Comparative Example 1, Example 1, Example 2 and Example 3 of the present invention; Figure 4 The water absorption and water retention curves of the anode catalyst layer obtained in Comparative Example 1, Example 4, Example 5, Example 6, Example 7 and Example 8 of the present invention; Figure 5 These are the Nyquist diagrams of the membrane electrodes obtained in Comparative Example 2, Example 9, Example 10, and Example 11 of the present invention.

[0020] Figure 6 This is a performance diagram of the dehumidification device obtained in Comparative Example 3, Example 6, Example 12, and Example 13 of the present invention. DETAILED DESCRIPTION

[0021] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not used to limit the scope of the present invention. Any other changes, modifications, substitutions, combinations, and simplifications made without violating the spirit and principle of the present invention should all be equivalent replacement methods and are included in the protection scope of the present invention. In addition, it should be understood that after reading the content of the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms also fall within the scope defined by the claims attached to this application, and all belong to the scope of protection of the present invention.

[0022] Reference to "embodiment" herein means that the specific features, structures or characteristics described in conjunction with the embodiment may be included in at least one embodiment of the present application. The term "embodiment" appearing in various places in the specification does not necessarily refer to the same embodiment, nor does it particularly limit its independence or association with other embodiments. In principle, in the present application, as long as there is no technical contradiction or conflict, the various technical features mentioned in the embodiments can be combined in any way to form a corresponding implementable technical solution.

[0023] Unless otherwise defined, the technical terms used in this document have the same meanings as those generally understood by those skilled in the art to which this application belongs; the use of relevant terms in this document is only for describing specific embodiments and is not intended to limit this application.

[0024] Unless otherwise specified in the present invention, the reagents, instruments, and equipment used are those commonly used by technicians in this field.

[0025] The electrolyte membrane in Examples 1-3 is a proton conducting polymer doped with 4.53wt.% to 14.94wt.% of a hygroscopic inorganic filler, and a slurry of a catalyst, a proton conducting polymer and a solvent is sprayed on the electrolyte membrane to prepare a membrane electrode. The anode catalyst layer of the membrane electrode specifically comprises: 80% catalyst particles and 20% proton conducting polymer; the cathode catalyst layer specifically comprises: 64% catalyst particles and 36% proton conducting polymer.

[0026] Among them, the proton conducting polymer used is perfluorosulfonic acid resin, the hygroscopic inorganic filler is SiO2, the inorganic filler size is 20nm, the catalyst used in the anode is iridium dioxide particles, the catalyst particle size is 60nm, and the catalyst used in the cathode is platinum carbon, the catalyst particle size is 5nm.

[0027] Example 1 This embodiment provides a method for preparing a PEM water vapor electrolyzer membrane electrode with a high water mass transfer coefficient, which specifically includes the following steps: (1) Preparation of high water-retaining proton exchange membrane: A Nafion membrane with a thickness of 127 μm was placed in a vacuum drying oven at 80°C for 12 hours, and then the membrane was immersed in a methanol / water solution with a volume ratio of 1:2 to swell for 1 hour, and then the sample was taken out and the solution remaining on the membrane surface was wiped dry with filter paper. The sample was then immersed in a methanol / tetraethyl silicate solution with a volume ratio of 6:1 for 5 minutes to perform an in-situ sol-gel reaction. After the reaction was completed, the sample was placed in a vacuum drying oven at 80°C for 48 hours to ensure that the in-situ sol-gel reaction was completed, and a highly water-absorbent PEM / SiO2 proton exchange membrane was obtained.

[0028] (2) Preparation of anode catalyst layer: Iridium dioxide and 5wt.% Nafion were taken in a mass ratio of 4:1, added to a mixed solution of isopropanol and water to disperse into a uniform catalyst slurry, loaded on one side of the proton exchange membrane obtained in step (1), and dried to form an anode catalyst layer. The ratio of iridium dioxide to Nafion was 4:1, so that the catalyst metal loading on the proton exchange membrane was 1.3mg / cm 2 .

[0029] (3) Preparation of cathode catalyst layer: 20% carbon-supported platinum and 5wt.% Nafion were added to a mixed solution of isopropanol and water at a mass ratio of 1.78:1 to form a uniform catalyst slurry, which was loaded on the other side of the proton exchange membrane obtained in step (1) and dried to form a cathode catalyst layer. The ratio of carbon-supported platinum to Nafion ionomer was controlled to be 1.78:1, so that the catalyst metal loading on the proton exchange membrane was 0.2 mg / cm 2 .

[0030] (4) The titanium mesh is bonded to one side of the proton exchange membrane carrying the anode catalyst layer, and the carbon paper treated with polytetrafluoroethylene is bonded to one side of the proton exchange membrane carrying the cathode catalyst layer to prepare a PEM water vapor electrolyzer membrane electrode.

[0031] Example 2 This embodiment provides a method for preparing a PEM water vapor electrolyzer membrane electrode with a high water mass transfer coefficient, which specifically includes the following steps: (1) Preparation of high water-retaining proton exchange membrane: A Nafion membrane with a thickness of 127 μm was placed in a vacuum drying oven at 80°C for 12 hours, and then the membrane was immersed in a methanol / water solution with a volume ratio of 3:2 to swell for 1 hour, and then the sample was taken out and the residual solution on the membrane surface was wiped dry with filter paper. The sample was then immersed in a methanol / tetraethyl silicate solution with a volume ratio of 4:1 for 5 minutes to perform an in-situ sol-gel reaction. After the reaction was completed, the sample was placed in a vacuum drying oven at 80°C for 48 hours to ensure that the in-situ sol-gel reaction was completed, and a highly water-absorbent PEM / SiO2 proton exchange membrane was obtained.

[0032] (2) Preparation of anode catalyst layer: Iridium dioxide and 5wt.% Nafion were taken in a mass ratio of 4:1, added to a mixed solution of isopropanol and water to disperse into a uniform catalyst slurry, loaded on one side of the proton exchange membrane obtained in step (1), and dried to form an anode catalyst layer. The ratio of iridium dioxide to Nafion was 4:1, so that the catalyst metal loading on the proton exchange membrane was 1.3mg / cm 2 .

[0033] (3) Preparation of cathode catalyst layer: 20% carbon-supported platinum and 5wt.% Nafion were added to a mixed solution of isopropanol and water at a mass ratio of 1.78:1 to form a uniform catalyst slurry, which was loaded on the other side of the proton exchange membrane obtained in step (1) and dried to form a cathode catalyst layer. The ratio of carbon-supported platinum to Nafion ionomer was controlled to be 1.78:1, so that the catalyst metal loading on the proton exchange membrane was 0.2 mg / cm 2 .

[0034] (4) The titanium mesh is bonded to one side of the proton exchange membrane carrying the anode catalyst layer, and the carbon paper treated with polytetrafluoroethylene is bonded to one side of the proton exchange membrane carrying the cathode catalyst layer to prepare a PEM water vapor electrolyzer membrane electrode.

[0035] Example 3 This embodiment provides a method for preparing a PEM water vapor electrolyzer membrane electrode, which specifically includes the following steps: (1) Preparation of high water-retaining proton exchange membrane: A Nafion membrane with a thickness of 127 μm was placed in a vacuum drying oven at 80°C for 12 hours, and then the membrane was immersed in a methanol / water solution with a volume ratio of 4:1 to swell for 1 hour, and then the sample was taken out and the residual solution on the membrane surface was wiped dry with filter paper. The sample was then immersed in a methanol / tetraethyl silicate solution with a volume ratio of 3:2 for 5 minutes to perform an in-situ sol-gel reaction. After the reaction was completed, the sample was placed in a vacuum drying oven at 80°C for 48 hours to ensure that the in-situ sol-gel reaction was completed, and a highly water-absorbent PEM / SiO2 proton exchange membrane was obtained.

[0036] (2) Preparation of anode catalyst layer: Iridium dioxide and 5wt.% Nafion were taken in a mass ratio of 4:1, added to a mixed solution of isopropanol and water to disperse into a uniform catalyst slurry, loaded on one side of the proton exchange membrane obtained in step (1), and dried to form an anode catalyst layer. The ratio of iridium dioxide to Nafion was 4:1, so that the catalyst metal loading on the proton exchange membrane was 1.3mg / cm 2 .

[0037] (3) Preparation of cathode catalyst layer: 20% carbon-supported platinum and 5wt.% Nafion were added to a mixed solution of isopropanol and water at a mass ratio of 1.78:1 to form a uniform catalyst slurry, which was loaded on the other side of the proton exchange membrane obtained in step (1) and dried to form a cathode catalyst layer. The ratio of carbon-supported platinum to Nafion ionomer was controlled to be 1.78:1, so that the catalyst metal loading on the proton exchange membrane was 0.2 mg / cm 2 .

[0038] (4) The titanium mesh is bonded to one side of the proton exchange membrane carrying the anode catalyst layer, and the carbon paper treated with polytetrafluoroethylene is bonded to one side of the proton exchange membrane carrying the cathode catalyst layer to prepare a PEM water vapor electrolyzer membrane electrode.

[0039] The anode catalyst layer in Examples 4-8 is composed of a hygroscopic inorganic filler, catalyst particles and a proton conductive polymer. Specifically, the hygroscopic inorganic filler accounts for 2% to 10% of the catalyst mass, the catalyst particles account for 78.74% to 74.07% of the catalyst layer mass, and the proton conductive polymer accounts for 19.68% to 18.52%. The slurry obtained by mixing the catalyst, the hygroscopic inorganic filler, the proton conductive polymer and the solvent is sprayed on the electrolyte membrane to prepare the membrane electrode.

[0040] The proton conducting polymer used is perfluorosulfonic acid resin, the hygroscopic inorganic filler is SiO2 with a size of 20 nm, the catalyst used at the anode is iridium dioxide particles with a catalyst particle size of 60 nm, and the catalyst used at the cathode is platinum carbon with a catalyst particle size of 5 nm.

[0041] Example 4 This embodiment provides a method for preparing a PEM water vapor electrolyzer membrane electrode, which specifically includes the following steps: (1) Preparation of the anode hydrophilic catalyst layer: Iridium dioxide, 5wt.% Nafion and silicon dioxide were added to a mixed solution of isopropanol and water and uniformly dispersed into a uniform catalyst slurry, which was loaded on one side of a Nafion membrane with a thickness of 127μm and dried to form an anode hydrophilic catalyst layer. The mass ratio of iridium dioxide to Nafion ionomer was controlled to be 4:1, so that the catalyst metal loading was 1.3mg / cm 2 , silicon dioxide accounts for 2% of the total mass of iridium dioxide solid and 5wt.% Nafion.

[0042] (2) Preparation of cathode catalyst layer: 20% carbon-supported platinum and 5wt.% Nafion were added to a mixed solution of isopropanol and water to disperse into a uniform catalyst slurry, which was loaded on the other side of a 127μm thick Nafion membrane and dried to form a cathode catalyst layer. The mass ratio of carbon-supported platinum to Nafion ionomer was controlled to be 1.78:1, so that the catalyst metal loading was 0.2mg / cm 2 .

[0043] (3) The titanium mesh is bonded to one side of the proton exchange membrane carrying the anode hydrophilic catalyst layer, and the carbon paper treated with polytetrafluoroethylene hydrophobicity is bonded to one side of the proton exchange membrane carrying the cathode catalyst layer to prepare a PEM water vapor electrolyzer membrane electrode.

[0044] Example 5 This embodiment provides a method for preparing a PEM water vapor electrolyzer membrane electrode, which specifically includes the following steps: (1) Preparation of the anode hydrophilic catalyst layer: Iridium dioxide, 5wt.% Nafion and silicon dioxide were added to a mixed solution of isopropanol and water and uniformly dispersed into a uniform catalyst slurry, which was loaded on one side of a Nafion membrane with a thickness of 127μm and dried to form an anode hydrophilic catalyst layer. The mass ratio of iridium dioxide to Nafion ionomer was controlled to be 4:1, so that the catalyst metal loading was 1.3mg / cm 2 , silica accounts for 4% of the total mass of iridium dioxide solid and 5wt.% Nafion.

[0045] (2) Preparation of cathode catalyst layer: 20% carbon-supported platinum and 5wt.% Nafion were added to a mixed solution of isopropanol and water to disperse into a uniform catalyst slurry, which was loaded on the other side of a 127μm thick Nafion membrane and dried to form a cathode catalyst layer. The mass ratio of carbon-supported platinum to Nafion ionomer was controlled to be 1.78:1, so that the catalyst metal loading was 0.2mg / cm 2 .

[0046] (3) The titanium mesh is bonded to one side of the proton exchange membrane carrying the anode hydrophilic catalyst layer, and the carbon paper treated with polytetrafluoroethylene hydrophobicity is bonded to one side of the proton exchange membrane carrying the cathode catalyst layer to prepare a PEM water vapor electrolyzer membrane electrode.

[0047] Example 6 This embodiment provides a method for preparing a PEM water vapor electrolyzer membrane electrode, which specifically includes the following steps: (1) Preparation of the anode hydrophilic catalyst layer: Iridium dioxide, 5wt.% Nafion and silicon dioxide were added to a mixed solution of isopropanol and water and uniformly dispersed into a uniform catalyst slurry, which was loaded on one side of a Nafion membrane with a thickness of 127μm and dried to form an anode hydrophilic catalyst layer. The mass ratio of iridium dioxide to Nafion ionomer was controlled to be 4:1, so that the catalyst metal loading was 1.3mg / cm 2 , silicon dioxide accounts for 6% of the total mass of iridium dioxide solid and 5wt.% Nafion.

[0048] (2) Preparation of cathode catalyst layer: 20% carbon-supported platinum and 5wt.% Nafion were added to a mixed solution of isopropanol and water to disperse into a uniform catalyst slurry, which was loaded on the other side of a 127μm thick Nafion membrane and dried to form a cathode catalyst layer. The mass ratio of carbon-supported platinum to Nafion ionomer was controlled to be 1.78:1, so that the catalyst metal loading was 0.2mg / cm 2 .

[0049] (3) The titanium mesh is bonded to one side of the proton exchange membrane carrying the anode hydrophilic catalyst layer, and the carbon paper treated with polytetrafluoroethylene hydrophobicity is bonded to one side of the proton exchange membrane carrying the cathode catalyst layer to prepare a PEM water vapor electrolyzer membrane electrode.

[0050] Example 7 This embodiment provides a method for preparing a PEM water vapor electrolyzer membrane electrode, which specifically includes the following steps: (1) Preparation of the anode hydrophilic catalyst layer: Iridium dioxide, 5wt.% Nafion and silicon dioxide were added to a mixed solution of isopropanol and water and uniformly dispersed into a uniform catalyst slurry, which was loaded on one side of a Nafion membrane with a thickness of 127μm and dried to form an anode hydrophilic catalyst layer. The mass ratio of iridium dioxide to Nafion ionomer was controlled to be 4:1, so that the catalyst metal loading was 1.3mg / cm 2 , silicon dioxide accounts for 8% of the total mass of iridium dioxide solid and 5wt.% Nafion.

[0051] (2) Preparation of cathode catalyst layer: 20% carbon-supported platinum and 5wt.% Nafion were added to a mixed solution of isopropanol and water to disperse into a uniform catalyst slurry, which was loaded on the other side of a 127μm thick Nafion membrane and dried to form a cathode catalyst layer. The mass ratio of carbon-supported platinum to Nafion ionomer was controlled to be 1.78:1, so that the catalyst metal loading was 0.2mg / cm 2 .

[0052] (3) The titanium mesh is bonded to one side of the proton exchange membrane carrying the anode hydrophilic catalyst layer, and the carbon paper treated with polytetrafluoroethylene hydrophobicity is bonded to one side of the proton exchange membrane carrying the cathode catalyst layer to prepare a PEM water vapor electrolyzer membrane electrode.

[0053] Example 8 This embodiment provides a method for preparing a PEM water vapor electrolyzer membrane electrode, which specifically includes the following steps: (1) Preparation of the anode hydrophilic catalyst layer: Iridium dioxide, 5wt.% Nafion and silicon dioxide were added to a mixed solution of isopropanol and water and uniformly dispersed into a uniform catalyst slurry, which was loaded on one side of a Nafion membrane with a thickness of 127μm and dried to form an anode hydrophilic catalyst layer. The mass ratio of iridium dioxide to Nafion ionomer was controlled to be 4:1, so that the catalyst metal loading was 1.3mg / cm 2 , silicon dioxide accounts for 10% of the total mass of iridium dioxide solid and 5wt.% Nafion.

[0054] (2) Preparation of cathode catalyst layer: 20% carbon-supported platinum and 5wt.% Nafion were added to a mixed solution of isopropanol and water to disperse into a uniform catalyst slurry, which was loaded on the other side of a 127μm thick Nafion membrane and dried to form a cathode catalyst layer. The mass ratio of carbon-supported platinum to Nafion ionomer was controlled to be 1.78:1, so that the catalyst metal loading was 0.2mg / cm 2 .

[0055] (3) The titanium mesh is bonded to one side of the proton exchange membrane carrying the anode hydrophilic catalyst layer, and the carbon paper treated with polytetrafluoroethylene hydrophobicity is bonded to one side of the proton exchange membrane carrying the cathode catalyst layer to prepare a PEM water vapor electrolyzer membrane electrode.

[0056] The anode catalyst layer in Examples 9 to 11 is composed of catalyst particles and proton conductive polymers. Specifically, 80% catalyst particles and 20% proton conductive polymers. A slurry obtained by mixing the catalyst, hygroscopic inorganic filler, proton conductive polymer and solvent is sprayed on the electrolyte membrane in a gradient to prepare a membrane electrode.

[0057] The proton conducting polymer used is perfluorosulfonic acid resin, the catalyst used at the anode is iridium dioxide particles with a catalyst particle size of 60nm, and the catalyst used at the cathode is platinum carbon with a catalyst particle size of 5nm.

[0058] Example 9 This embodiment provides a method for preparing a PEM water vapor electrolyzer membrane electrode, which specifically includes the following steps: (1) Preparation of anode gradient catalytic layer: The first layer of catalytic slurry: iridium dioxide, 5wt.% Nafion and a mixed solution of isopropanol and water are dispersed into a uniform catalyst slurry, and the mass ratio of iridium dioxide to Nafion ionomer is controlled to be 5:1.

[0059] The second layer of catalytic slurry: a mixed solution of iridium dioxide, 5wt.% Nafion, isopropanol and water was dispersed into a uniform catalyst slurry, and the mass ratio of iridium dioxide to Nafion ionomer was controlled to be 7.5:1.

[0060] The first layer of catalytic slurry is sprayed on the Nafion membrane with a thickness of 127μm, which is called the first catalytic layer of the anode, providing highly active catalytic sites. The second layer of catalytic slurry is sprayed on the first catalytic layer of the anode to form the second catalytic layer of the anode, which optimizes the surface pore structure and promotes the transmission of water vapor. The catalyst metal loading is 1.3mg / cm 2 , and obtain an anode gradient catalytic layer.

[0061] (2) Preparation of cathode catalyst layer: A mixed solution of 20% carbon-supported platinum, 5wt.% Nafion, isopropanol and water was dispersed into a uniform catalyst slurry, loaded on the other side of a 127μm thick Nafion membrane, and dried to form a cathode catalyst layer. The mass ratio of carbon-supported platinum to Nafion ionomer was controlled to be 1.78:1, so that the catalyst metal loading was 0.2mg / cm 2 .

[0062] (3) The titanium mesh is bonded to one side of the proton exchange membrane carrying the anode gradient catalyst layer, and the carbon paper treated with polytetrafluoroethylene is bonded to one side of the proton exchange membrane carrying the cathode catalyst layer to prepare a PEM water vapor electrolyzer membrane electrode.

[0063] Example 10 This embodiment provides a method for preparing a PEM water vapor electrolyzer membrane electrode, which specifically includes the following steps: (1) Preparation of anode gradient catalytic layer: The first layer of catalytic slurry: iridium dioxide, 5wt.% Nafion and a mixed solution of isopropanol and water are dispersed into a uniform catalyst slurry, and the mass ratio of iridium dioxide to Nafion ionomer is controlled to be 4.29:1.

[0064] The second layer of catalytic slurry: a mixed solution of iridium dioxide, 5wt.% Nafion, isopropanol and water was dispersed into a uniform catalyst slurry, and the mass ratio of iridium dioxide to Nafion ionomer was controlled to be 10:1.

[0065] The first layer of catalytic slurry is sprayed on the Nafion membrane with a thickness of 127μm, which is called the first catalytic layer of the anode, providing highly active catalytic sites. The second layer of catalytic slurry is sprayed on the first catalytic layer of the anode to form the second catalytic layer of the anode, which optimizes the surface pore structure and promotes the transmission of water vapor. The catalyst metal loading is 1.3mg / cm 2 , and obtain an anode gradient catalytic layer.

[0066] (2) Preparation of cathode catalyst layer: A mixed solution of 20% carbon-supported platinum, 5wt.% Nafion, isopropanol and water was dispersed into a uniform catalyst slurry, loaded on the other side of a 127μm thick Nafion membrane, and dried to form a cathode catalyst layer. The mass ratio of carbon-supported platinum to Nafion ionomer was controlled to be 1.78:1, so that the catalyst metal loading was 0.2mg / cm 2 .

[0067] (3) The titanium mesh is bonded to one side of the proton exchange membrane carrying the anode gradient catalyst layer, and the carbon paper treated with polytetrafluoroethylene is bonded to one side of the proton exchange membrane carrying the cathode catalyst layer to prepare a PEM water vapor electrolyzer membrane electrode.

[0068] Embodiment 11 This embodiment provides a method for preparing a PEM water vapor electrolyzer membrane electrode, which specifically includes the following steps: (1) Preparation of anode gradient catalytic layer: The first layer of catalytic slurry: a mixed solution of iridium dioxide, 5wt.% Nafion, isopropanol and water was dispersed into a uniform catalyst slurry, and the mass ratio of iridium dioxide to Nafion ionomer was controlled to be 3.75:1.

[0069] The second layer of catalytic slurry: a mixed solution of iridium dioxide, 5wt.% Nafion, isopropanol and water was dispersed into a uniform catalyst slurry, and the mass ratio of iridium dioxide to Nafion ionomer was controlled to be 15:1.

[0070] The first layer of catalytic slurry is sprayed on the Nafion membrane with a thickness of 127μm, which is called the first catalytic layer of the anode, providing highly active catalytic sites. The second layer of catalytic slurry is sprayed on the first catalytic layer of the anode to form the second catalytic layer of the anode, which optimizes the surface pore structure and promotes the transmission of water vapor. The catalyst metal loading is 1.3mg / cm 2 , and obtain an anode gradient catalytic layer.

[0071] (2) Preparation of cathode catalyst layer: A mixed solution of 20% carbon-supported platinum, 5wt.% Nafion, isopropanol and water was dispersed into a uniform catalyst slurry, loaded on the other side of a 127μm thick Nafion membrane, and dried to form a cathode catalyst layer. The mass ratio of carbon-supported platinum to Nafion ionomer was controlled to be 1.78:1, so that the catalyst metal loading was 0.2mg / cm 2 .

[0072] (3) The titanium mesh is bonded to one side of the proton exchange membrane carrying the anode gradient catalyst layer, and the carbon paper treated with polytetrafluoroethylene is bonded to one side of the proton exchange membrane carrying the cathode catalyst layer to prepare a PEM water vapor electrolyzer membrane electrode.

[0073] The electrolyte membrane in Examples 12 and 13 is a proton conducting polymer doped with 4.53wt.% to 14.94wt.% of a hygroscopic inorganic filler, and a slurry of a catalyst, a hygroscopic inorganic filler, a proton conducting polymer and a solvent is sprayed on the electrolyte membrane to prepare a membrane electrode. The anode catalyst layer of the membrane electrode specifically comprises: a hygroscopic inorganic filler accounting for 2% to 10% of the catalyst mass, catalyst particles accounting for 78.74% to 74.07% of the catalyst layer mass, and 19.68% to 18.52% of a proton conducting polymer.

[0074] Among them, the proton conducting polymer used is perfluorosulfonic acid resin, the hygroscopic inorganic filler is SiO2, the inorganic filler size is 20nm, the catalyst used in the anode is iridium dioxide particles, the catalyst particle size is 60nm, and the catalyst used in the cathode is platinum carbon, the catalyst particle size is 5nm.

[0075] Example 12 This embodiment provides a method for preparing a PEM water vapor electrolyzer membrane electrode, which specifically includes the following steps: (1) Preparation of high water-retaining proton exchange membrane: The 127 μm Nafion membrane was placed in a vacuum drying oven at 80 °C and dried for 12 hours. The membrane was then immersed in a methanol / water solution to swell for 1 hour. Subsequently, the sample was taken out and the residual solution on the membrane surface was wiped off with filter paper. The sample was then immersed in a methanol / tetraethyl silicate solution for 5 minutes for an in-situ sol-gel reaction. After the reaction, the sample was placed in a vacuum drying oven at 80 °C and dried for 48 hours to ensure that the in-situ sol-gel reaction was completed to obtain a highly water-absorbent PEM / SiO2 composite membrane. The water / methanol ratio was controlled to be 2:1, and the methanol / tetraethyl silicate ratio was also controlled to be 2:1.

[0076] (2) Preparation of anode hydrophilic catalyst layer: A mixed solution of iridium dioxide, 5wt.% Nafion, silicon dioxide, isopropanol and water was dispersed into a uniform catalyst slurry, loaded on one side of a 127μm Nafion membrane, and dried to form a catalyst layer solid. The ratio of iridium dioxide to Nafion ionomer was controlled to be 4:1, silicon dioxide accounted for 6% of the total mass of iridium dioxide solid and 5wt.% Nafion, and the catalyst metal loading was controlled to be 1.3mg / cm 2 , and obtain the anode hydrophilic catalytic layer.

[0077] (3) Preparation of cathode catalyst layer: A mixed solution of 20% carbon-supported platinum, 5wt.% Nafion, isopropanol and water was dispersed into a uniform catalyst slurry, loaded on the other side of the 127μm Nafion membrane, and dried to form a solid catalyst layer. The ratio of carbon-supported platinum to Nafion ionomer was controlled to 1.78:1, and the catalyst metal loading was controlled to 0.2mg / cm 2 , and obtain a cathode catalyst layer.

[0078] (4) The titanium mesh is bonded to one side of the proton exchange membrane carrying the anode gradient catalyst layer, and the carbon paper treated with polytetrafluoroethylene hydrophobicity is bonded to one side of the proton exchange membrane carrying the cathode catalyst layer to prepare a PEM water vapor electrolyzer membrane electrode.

[0079] Embodiment 13 This embodiment provides a method for preparing a PEM water vapor electrolyzer membrane electrode, which specifically includes the following steps: (1) Preparation of high water-retaining proton exchange membrane: The 127 μm Nafion membrane was placed in a vacuum drying oven at 80 °C and dried for 12 hours. The membrane was then immersed in a methanol / water solution to swell for 1 hour. Subsequently, the sample was taken out and the residual solution on the membrane surface was wiped off with filter paper. The sample was then immersed in a methanol / tetraethyl silicate solution for 5 minutes for an in-situ sol-gel reaction. After the reaction, the sample was placed in a vacuum drying oven at 80 °C and dried for 48 hours to ensure that the in-situ sol-gel reaction was completed to obtain a highly water-absorbent PEM / SiO2 composite membrane. The water / methanol ratio was controlled to be 2:3 and the methanol / tetraethyl silicate ratio was controlled to be 4:1.

[0080] (2) Preparation of anode hydrophilic catalyst layer: A mixed solution of iridium dioxide, 5wt.% Nafion, silicon dioxide, isopropanol and water was dispersed into a uniform catalyst slurry, loaded on one side of a 127μm Nafion membrane, and dried to form a catalyst layer solid. The ratio of iridium dioxide to Nafion ionomer was controlled to be 4:1, silicon dioxide accounted for 6% of the total mass of iridium dioxide solid and 5wt.% Nafion, and the catalyst metal loading was controlled to be 1.3mg / cm 2 , and obtain the anode hydrophilic catalytic layer.

[0081] (3) Preparation of cathode catalyst layer: A mixed solution of 20% carbon-supported platinum, 5wt.% Nafion, isopropanol and water was dispersed into a uniform catalyst slurry, loaded on the other side of the 127μm Nafion membrane, and dried to form a solid catalyst layer. The ratio of carbon-supported platinum to Nafion ionomer was controlled to 1.78:1, and the catalyst metal loading was controlled to 0.2mg / cm 2 , and obtain a cathode catalyst layer.

[0082] (4) The titanium mesh is bonded to one side of the proton exchange membrane carrying the anode gradient catalyst layer, and the carbon paper treated with polytetrafluoroethylene hydrophobicity is bonded to one side of the proton exchange membrane carrying the cathode catalyst layer to prepare a PEM water vapor electrolyzer membrane electrode.

[0083] Comparative Example 1 This comparative example provides a method for preparing a PEM water vapor electrolyzer membrane electrode, which specifically comprises the following steps: (1) Preparation of anode catalyst layer: A mixed solution of iridium dioxide, 5wt.% Nafion, isopropanol and water was dispersed into a uniform catalyst slurry, loaded on one side of a Nafion membrane with a thickness of 127μm, and dried to form a solid catalyst layer. The mass ratio of iridium dioxide to Nafion ionomer was controlled to be 4:1, so that the catalyst metal loading was 1.3mg / cm 2 .

[0084] (2) Preparation of cathode catalyst layer: 20% carbon-supported platinum and 5wt.% Nafion were added to a mixed solution of isopropanol and water to disperse into a uniform catalyst slurry, which was loaded on the other side of a 127μm thick Nafion membrane and dried to form a cathode catalyst layer. The mass ratio of carbon-supported platinum to Nafion ionomer was controlled to be 1.78:1, so that the catalyst metal loading was 0.2mg / cm 2 .

[0085] (3) The titanium mesh is bonded to one side of the proton exchange membrane carrying the anode catalyst layer, and the carbon paper treated with polytetrafluoroethylene is bonded to one side of the proton exchange membrane carrying the cathode catalyst layer to prepare a PEM water vapor electrolyzer membrane electrode.

[0086] Comparative Example 2 This comparative example provides a method for preparing a PEM water vapor electrolyzer membrane electrode, which specifically comprises the following steps: (1) Preparation of anode gradient catalytic layer: The first layer of catalytic slurry: a mixed solution of iridium dioxide, 5wt.% Nafion, isopropanol and water was dispersed into a uniform catalyst slurry, and the mass ratio of iridium dioxide to Nafion ionomer was controlled to be 6:1.

[0087] The second layer of catalytic slurry: a mixed solution of iridium dioxide, 5wt.% Nafion, isopropanol and water was dispersed into a uniform catalyst slurry, and the mass ratio of iridium dioxide to Nafion ionomer was controlled to be 6:1.

[0088] The first layer of catalytic slurry is sprayed on the Nafion membrane with a thickness of 127μm, which is called the first catalytic layer of the anode, providing highly active catalytic sites. The second layer of catalytic slurry is sprayed on the first catalytic layer of the anode to form the second catalytic layer of the anode, which optimizes the surface pore structure and promotes the transmission of water vapor. The catalyst metal loading is 1.3mg / cm 2 , and obtain an anode gradient catalytic layer.

[0089] (2) Preparation of cathode catalyst layer: A mixed solution of 20% carbon-supported platinum, 5wt.% Nafion, isopropanol and water was dispersed into a uniform catalyst slurry, loaded on the other side of a 127μm thick Nafion membrane, and dried to form a cathode catalyst layer. The mass ratio of carbon-supported platinum to Nafion ionomer was controlled to be 1.78:1, so that the catalyst metal loading was 0.2mg / cm 2 .

[0090] (3) The titanium mesh is bonded to one side of the proton exchange membrane carrying the anode gradient catalyst layer, and the carbon paper treated with polytetrafluoroethylene is bonded to one side of the proton exchange membrane carrying the cathode catalyst layer to prepare a PEM water vapor electrolyzer membrane electrode.

[0091] Comparative Example 3 This comparative example provides a method for preparing a PEM water vapor electrolyzer membrane electrode, which specifically comprises the following steps: (1) Preparation of high water-retaining proton exchange membrane: The 127 μm Nafion membrane was placed in a vacuum drying oven at 80 °C and dried for 12 hours. The membrane was then immersed in a methanol / water solution to swell for 1 hour. Subsequently, the sample was taken out and the residual solution on the membrane surface was wiped off with filter paper. The sample was then immersed in a methanol / tetraethyl silicate solution for 5 minutes for an in-situ sol-gel reaction. After the reaction, the sample was placed in a vacuum drying oven at 80 °C and dried for 48 hours to ensure that the in-situ sol-gel reaction was completed to obtain a highly water-absorbent PEM / SiO2 composite membrane. The ratio of methanol / water was controlled to be 1:2, and the ratio of methanol / tetraethyl silicate was controlled to be 2:3.

[0092] (2) Preparation of anode hydrophilic catalyst layer: A mixed solution of iridium dioxide, 5wt.% Nafion, silicon dioxide, isopropanol and water was dispersed into a uniform catalyst slurry, loaded on one side of a 127μm Nafion membrane, and dried to form a catalyst layer solid. The ratio of iridium dioxide to Nafion ionomer was controlled to be 4:1, silicon dioxide accounted for 6% of the total mass of iridium dioxide solid and 5wt.% Nafion, and the catalyst metal loading was controlled to be 1.3mg / cm 2 , and obtain the anode hydrophilic catalytic layer.

[0093] (3) Preparation of cathode catalyst layer: A mixed solution of 20% carbon-supported platinum, 5wt.% Nafion, isopropanol and water was dispersed into a uniform catalyst slurry, loaded on the other side of the 127μm Nafion membrane, and dried to form a solid catalyst layer. The ratio of carbon-supported platinum to Nafion ionomer was controlled to 1.78:1, and the catalyst metal loading was controlled to 0.2mg / cm 2 , and obtain a cathode catalyst layer.

[0094] (4) The titanium mesh is bonded to one side of the proton exchange membrane carrying the anode gradient catalyst layer, and the carbon paper treated with polytetrafluoroethylene hydrophobicity is bonded to one side of the proton exchange membrane carrying the cathode catalyst layer to prepare a PEM water vapor electrolyzer membrane electrode.

[0095] Figure 1 This is a schematic diagram of the water and proton transfer in the anode catalyst layer of the electrolytic water vapor membrane assembly. It shows that during the operation of the membrane assembly, water vapor enters the catalyst layer after passing through the diffusion layer, diffuses in the pore structure, passes through the ionomer covered on the catalyst surface and contacts the active site, and oxygen evolution reaction occurs under the catalytic action. The product oxygen diffuses from the pores, and hydrogen protons are transferred through the ionomer and pass through the proton exchange membrane to participate in the next reaction.

[0096] Figure 2 The SEM images of the hydrophilic anode catalyst layer with 6 wt.% SiO2 addition and the anode catalyst layer without SiO2 addition in Example 6 are shown in FIG. It can be seen from the figure that after the addition, the SiO2 particles are evenly dispersed in the catalyst layer, reducing the phenomenon of agglomeration caused by uneven distribution of ionomer and catalyst, and forming more porous structures to diffuse water vapor.

[0097] Figure 3It is the adsorption isotherm of the hydration coefficient of the PEM / SiO2 composite membrane obtained in Comparative Example 1, Example 1, Example 2 and Example 3. As can be seen from the figure, with the increase of air humidity, the hydration coefficient λ of the membrane shows a similar increasing trend. Under 40%RH conditions, compared with Comparative Example 1, the hydration coefficients of Example 1, Example 2 and Example 3 increase by 13.67%, 43.33% and 78%, respectively. Under different humidity conditions, the moisture absorption rate of Example 2 is 38.7% to 60.1% higher than that of Comparative Example 1. This proves that the introduction of SiO2 significantly increases the moisture absorption rate of PEM under low humidity, helps to maintain the hydration of the membrane, and slows down the proton transmission loss caused by membrane drying.

[0098] Figure 4 The water absorption and water retention curves of the anode catalyst layer obtained from Comparative Example 1, Example 4, Example 5, Example 6, Example 7 and Example 8. From the water retention results, it can be seen that the water retention of the anode catalyst layer in Comparative Example 1 is 28.9%, while the water retention of Example 8 is 156.5%, indicating that the addition of SiO2 can significantly increase the moisture content of CL. From the moisture absorption results, it can be seen that with the increase in the amount of SiO2 added, the moisture absorption rate of the membrane electrode continues to increase. The moisture absorption rate of the anode catalyst layer in Comparative Example 1 is 8.3%, while the moisture absorption rate of Example 8 is 32%, which shows that SiO2 enhances the moisture absorption rate of the membrane electrode, improves the ability of the anode catalyst layer to absorb water vapor from the air, and reduces the difficulty of mass transfer of reactants.

[0099] Figure 5 The Nyquist plots of the membrane electrodes obtained in Comparative Example 2, Example 9, Example 10, and Example 11. As can be seen from the figure, the ohmic resistance of the membrane assemblies obtained in the comparative example and the example are not much different. Compared with Comparative Example 2, the electrochemical reaction impedances of Example 9 and Example 10 were reduced by 14.7% and 7.5%, respectively, while the reaction impedance of Example 11 increased by 20.4%. This shows that excessive Nafion content gradient will reduce the performance of the device, while an appropriate gradient can reduce the gas and proton transport resistance of the membrane assembly. The following dehumidification performance test was performed on the membrane electrodes obtained in the above examples and comparative examples.

[0100] Figure 6 This is a graph of the dehumidification rate of the electrolyte membrane dehumidification device obtained in Comparative Example 3, Example 6, Example 12 and Example 13. Wet air at 10°C, 80%RH and a flow rate of 0.016g / s was introduced into the anode and cathode inlets of the obtained electrolyte membrane dehumidification device, and 3V of direct current was applied to the device. The changes in the humidity at the anode and cathode outlets were recorded at the same time, and the dehumidification rate of the device was calculated. In a low temperature environment, the activation energy of the electrochemical reaction increases, and the speed of electron transfer and proton transfer slows down. It is normal for the device to have a lower dehumidification rate than at normal temperature. Figure 6It can be seen that at 10°C and 80%RH, the dehumidification rate of Comparative Example 3 is 0.99×10 -4 g / s, the dehumidification rate of Example 13 is 0.24×10 -4 g / s, which is 1.5 times higher than that of Comparative Example 3 and 17.5% higher than that of Example 6. It shows that in the case of slow material transfer in a low-temperature environment, adding hydrophilic SiO2 in the catalyst layer can help capture water molecules, provide more reactants for the anode reaction, and work together with the SiO2 doped in the electrolyte membrane to enhance the water retention capacity of the ionomer in the catalyst layer and the electrolyte membrane, stretch the main chain of the ionomer, disperse the side chain of the hydrophilic sulfonic acid group, construct a continuous proton transfer channel from the catalyst layer to the membrane and shorten the transfer path, effectively alleviate the decrease in the mass transfer rate in the catalyst layer and the membrane to achieve the effect of improving the dehumidification performance of the device in a low-temperature environment. The dehumidification performance of Example 12 has decreased, indicating that co-doping SiO2 in the catalyst layer and the electrolyte membrane can effectively improve the low-temperature dehumidification performance, but excessive doping may enhance the reverse diffusion phenomenon and have the opposite effect of hindering mass transfer. Therefore, the reasonable regulation of the SiO2 content in the high water retention proton exchange membrane and the anode hydrophilic catalyst layer plays an important role in the dehumidification performance of the device, so further optimization can expand the advantage of enhanced mass transfer to obtain higher dehumidification performance.

[0101] The prepared membrane electrode was hot pressed at 110°C, 0.4MPa, and 180s. Subsequently, bipolar plates were loaded on both sides of the membrane electrode, and then encapsulated with acrylic plates to obtain an electrolyte membrane dehumidification device. Wet air at 20°C, 80%RH, and a flow rate of 0.016g / s was introduced into the anode and cathode inlets of the obtained electrolyte membrane dehumidification device, and 3V of direct current was applied to the device. At the same time, the changes in the humidity at the anode and cathode outlets were recorded, and the dehumidification rate of the device was calculated. The results are shown in Table 1.

[0102] Table 1 ;

[0103] From the data in Table 1, it can be seen that under 80% RH conditions, the dehumidification rate of Example 2 is 8% higher than that of the device in Comparative Example 1. Under 50% RH conditions, the dehumidification rate of Comparative Example 1 is 0.456×10 -4 g / s, while the dehumidification rate of Example 2 is 0.54×10 -4g / s, which is 18.4% higher than that of Comparative Example 1. This shows that under low humidity, the water retention capacity of nano-SiO2 particles plays an important role, which can absorb water and retain it in the membrane, thereby improving the phenomenon of severe water shortage of the membrane. However, compared with Comparative Example 1, the dehumidification rate of the device of Example 3 decreased by 13.1% and 45.4% respectively under 80%RH and 50%RH conditions, and the water content in the proton exchange membrane significantly affects the ability to transfer protons, especially under low humidity and water shortage conditions, adding SiO2 hydrophilic particles increases the water content of the membrane, promotes the ionomer side chain to absorb water to form a proton transfer network, thereby significantly improving the dehumidification rate, and too much addition of nanoparticles will affect the arrangement of the ionomer in the membrane, causing incompatible phenomena to occur, hindering proton transfer, therefore, it is necessary to select the optimal addition amount within a suitable concentration range. Increase the water content of the membrane.

[0104] Under 80%RH conditions, the dehumidification rate of Example 5 is not much different from that of Comparative Example 1. The dehumidification rate of Example 6 is 11% higher than that of Comparative Example 1, which indicates that the addition of SiO2 can increase the water retention and water absorption of the membrane electrode, making it easier for protons to pass through the wetted ionomer. The dehumidification rate of Example 8 is 17.1% lower than that of Comparative Example 1. This shows that there is an optimal range for the addition of SiO2. Excessive insulating SiO2 will seriously affect the electronic conductivity of the membrane electrode, thereby affecting the dehumidification rate. In addition, excessive SiO2 will cover the active sites, block the pores, and adversely affect the gas mass transfer. Under 50%RH conditions, the dehumidification rate of Example 6 is 0.567×10 -4g / s, an increase of 24.3% over Comparative Example 1. The performance improvement rate of the dehumidification device with hydrophilic SiO2 added at 50%RH is significantly higher than that at 80%RH. This shows that under low humidity, the dry membrane electrode will significantly reduce the proton conductivity, and the reduction of reactant water vapor is the rate-limiting factor of the dehumidification reaction. The moderate addition of hydrophilic nano-SiO2 enhances the moisture content and moisture absorption rate of the membrane electrode, keeps the ionomer wet, maintains the proton transport in the membrane electrode, and enhances the ability of the membrane electrode to "capture" water vapor from the air, reducing the difficulty of mass transfer of water vapor from the diffusion layer into the catalytic site. Compared with Comparative Example 2, the dehumidification rate of Example 9 increased by 14.8% at 80%RH and by 12% at 50%RH, which shows that reasonable control of the catalytic layer gradient design can improve the dehumidification effect. The second layer of more iridium dioxide provides dense active sites, promotes the electrochemical reaction of water molecules passing through the diffusion layer, and the first layer of catalyst layer ionomer accounts for a relatively large proportion, and more proton transmission channels can be formed in the area close to the membrane, increasing the reaction current and enhancing the dehumidification performance. The dehumidification rate of Example 11 is reduced by 18.7%~22.5%. This shows the importance of reasonable control of the gradient. Too much ionomer in the first layer of catalyst layer will lead to insufficient dispersion and uniform coverage of the iridium dioxide active sites, forming a thicker ionomer film and blocking the pores, increasing the gas diffusion resistance. Too little ionomer in the second layer of catalyst layer will lead to the inability to continuously transfer the generated protons, and even the catalyst shedding phenomenon. This shows that the catalytic layer gradient design has the characteristics of being difficult to control in the microstructure, but further reasonable regulation of the optimal iridium dioxide and Nafion ionomer ratio is expected to achieve a higher performance dehumidification effect without increasing the catalyst loading. This shows that the appropriate gradient catalytic layer design can make the ionomer membrane of the first catalytic layer of the anode thicker than the second catalytic layer, reducing the transmission resistance of protons through the first catalytic layer, while the ionomer content of the second catalytic layer is small, and the resistance of gas transmission to the catalytic site is small. However, when the ionomer span is too large, too much ionomer in the first catalytic layer may cover the catalyst active site, affecting the exposure of the catalyst active site, and also hindering the gas from entering the first catalytic layer, while too little ionomer in the second catalytic layer will affect the transfer of protons in the second catalytic layer, resulting in a decrease in the dehumidification rate. Compared with Comparative Example 3, the dehumidification performance of the device of Example 12 under 80% RH conditions at a dehumidification environment temperature of 20°C is reduced. This is because the excessive addition of hydrophilic particles affects the arrangement of ionomers in the membrane, resulting in incompatibility. Compared with Comparative Example 3, the dehumidification rate of the device of Example 13 is increased by 10.3%, and the overall trend is consistent with the low temperature environment of 10°C, which shows that the content of SiO2 doped in the membrane under different temperature environments will significantly affect the dehumidification performance of devices with water-retaining modified membranes and catalytic layers.The membrane and the catalyst layer are modified with appropriate hydrophilic particle doping amount and water retention at the same time, which can stretch the ionomer chains of each part, improve the utilization rate of sulfonic acid groups, accelerate mass transfer, and shorten the overall transfer path of protons from the catalyst layer to the membrane, thereby enhancing the dehumidification performance. The dehumidification rate of Example 13 at 10°C is 17.5% higher than that of Example 6 because the temperature decrease will cause the proton transfer rate to decrease, but after the modification of the membrane and the catalyst layer, a stable transfer channel can be provided while shortening the overall mass transfer path, and the reaction in the device is completed faster, thereby enhancing the dehumidification performance. Further regulation of the SiO2 content in the catalyst layer and the membrane can optimize the dehumidification capacity of the device under various environmental conditions.

[0105] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.

Claims

1. A method for preparing a PEM water vapor electrolyzer membrane electrode with a high water mass transfer coefficient, characterized in that: The specific steps include: (1) Preparation of high water retention proton exchange membrane The perfluorosulfonic acid membrane is dried, then immersed in a methanol / water solution for swelling, taken out, and then immersed in a methanol / tetraethyl silicate solution for in-situ sol-gel reaction. After the reaction is completed, the membrane is taken out for drying to obtain a high water-retention proton exchange membrane; (2) Preparation of anode hydrophilic catalytic layer The metal anode catalyst, perfluorosulfonic acid ionomer, silicon dioxide and solvent are mixed and dispersed into a uniform catalyst slurry, which is loaded on one side of the high water retention proton exchange membrane obtained in step (1), and dried to form an anode hydrophilic catalyst layer; (3) Preparation of cathode catalyst layer Mixing and dispersing a metal cathode catalyst, a perfluorosulfonic acid ionomer and a solvent into a uniform catalyst slurry, loading the slurry on the other side of the high water retention proton exchange membrane obtained in step (1), and drying the slurry to form a cathode catalyst layer; (4) Preparation of PEM water vapor electrolyzer membrane electrode The anode gas diffusion layer and the cathode gas diffusion layer are respectively bonded to the catalyst layers obtained in step (2) and step (3) to obtain a PEM water vapor electrolyzer membrane electrode.

2. The method for preparing a PEM water vapor electrolyzer membrane electrode with a high water mass transfer coefficient according to claim 1, characterized in that: In step (1), the volume ratio of methanol to water in the methanol / water solution is 1-4:1-3, and the volume ratio of methanol to tetraethyl silicate in the methanol / tetraethyl silicate solution is 2-6:1-3.

3. The method for preparing a PEM water vapor electrolyzer membrane electrode with a high water mass transfer coefficient according to claim 1, characterized in that: In step (1), the thickness of the perfluorosulfonic acid film is 127 μm; the drying condition of the perfluorosulfonic acid film is drying in a vacuum drying oven at 80° C. for 12 h; and the drying condition after the reaction is completed is drying in a vacuum drying oven at 80° C. for 48 h.

4. The method for preparing a PEM water vapor electrolyzer membrane electrode with a high water mass transfer coefficient according to claim 1, characterized in that: In step (2), the loading amount of the metal in the metal anode catalyst on the high water retention proton exchange membrane is 1.3 mg / cm 2 .

5. The method for preparing a PEM water vapor electrolyzer membrane electrode with a high water mass transfer coefficient according to claim 1, characterized in that: In step (2), the mass ratio of the metal anode catalyst to the perfluorosulfonic acid ionomer is 4:1, and the silicon dioxide accounts for 0%-10% of the total mass of the metal anode catalyst and the perfluorosulfonic acid ionomer.

6. The method for preparing a PEM water vapor electrolyzer membrane electrode with a high water mass transfer coefficient according to claim 1, characterized in that: In step (2), the particle size of silicon dioxide is 20 nm; the metal anode catalyst is iridium dioxide; the perfluorosulfonic acid ionomer is 5 wt.% Nafion; and the solvent is a mixed solution of isopropanol and water.

7. The method for preparing a PEM water vapor electrolyzer membrane electrode with a high water mass transfer coefficient according to claim 1, characterized in that: In step (3), the loading amount of the metal in the metal cathode catalyst on the high water retention proton exchange membrane is 0.2 mg / cm 2 .

8. The method for preparing a PEM water vapor electrolyzer membrane electrode with a high water mass transfer coefficient according to claim 1, characterized in that: In step (3), the mass ratio of the metal cathode catalyst to the perfluorosulfonic acid ionomer is 1.78:

1.

9. The method for preparing a PEM water vapor electrolyzer membrane electrode with a high water mass transfer coefficient according to claim 1, characterized in that: In step (3), the metal cathode catalyst is a 20% carbon-supported platinum catalyst; the perfluorosulfonic acid ionomer is 5wt.% Nafion; and the solvent is a mixture of isopropanol and water.

10. The method for preparing a PEM water vapor electrolyzer membrane electrode with a high water mass transfer coefficient according to claim 1, characterized in that: In step (4), the anode gas diffusion layer is a titanium mesh; and the cathode gas diffusion layer is a carbon paper treated with polytetrafluoroethylene for hydrophobicity.

Citation Information

Patent Citations

  • Anode catalyst configured humidifying-free membrane electrode and preparation method thereof

    CN107482228A

  • Preparation method of self-humidifying membrane electrode for fuel cell

    CN110289438A

  • Composite proton exchange film for anti-gas osmosising fuel cell and production thereof

    CN1707837A

  • Polymer solid-electrolyte composition and electrochemical cell using the composition

    US5523181A